2014
DOI: 10.1097/fjc.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Functional Study of TREK-1 Potassium Channels During Rat Heart Development and Cardiac Ischemia Using RNAi Techniques

Abstract: To explore the physiological and pathological significance of the 2-pore domain potassium channel TWIK-related K(+) (TREK)-1 in rat heart, its expression and role during heart development and cardiac ischemia were investigated. In the former study, the ventricles of Sprague Dawley rats were collected from embryo day 19 to postnatal 18 months and examined for mRNA and protein expression of TREK-1. It was found that both increased during development, reached a maximum at postnatal day 28, and remained higher at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The most striking finding was that TREK-1 KO hearts were more susceptible to I/R-induced cardiac damage than the control counterpart. This is somewhat different from a previous finding showing that TREK-1 knockdown in neonatal rat cardiomyocytes is protective against ischemic damage in vitro [35]. Nevertheless, neonatal rat cardiomyocytes are not fully differentiated characterized by an hypometabolic status and are more tolerant to ischemia than the adult mouse hearts [2,23].…”
Section: Discussioncontrasting
confidence: 96%
“…The most striking finding was that TREK-1 KO hearts were more susceptible to I/R-induced cardiac damage than the control counterpart. This is somewhat different from a previous finding showing that TREK-1 knockdown in neonatal rat cardiomyocytes is protective against ischemic damage in vitro [35]. Nevertheless, neonatal rat cardiomyocytes are not fully differentiated characterized by an hypometabolic status and are more tolerant to ischemia than the adult mouse hearts [2,23].…”
Section: Discussioncontrasting
confidence: 96%
“…KCNK2 also acts as a cytoplasmic pH sensor whereby increasing intracellular acidity induces channel activation 8 , 9 . This particular property suggests a putative protective role for KCNK2 against ischemia and pain, in which disrupted metabolism promotes intracellular acidification 29 , 42 44 . Consequently, the increasing acidity triggers KCNK2 to open resulting in cell membrane hyperpolarisation, a protective phenomenon also produced by ATP sensitive potassium channels during cardiac and cerebral ischemia 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological point of view, sensitization of TREK-1 by LecA might be a starting point for novel therapeutic targeting of atrial fibrillation or heart failure -two pathologies where TREK-1 has been reported to be suppressed (Lugenbiel et al, 2017). Furthermore, TREK-1 inhibits proliferation of neuronal stem cells, astrocytes, osteoblasts, Chinese hamster ovary cells, and neonatal cardiomyocytes (Hughes et al, 2006;Xi et al, 2011;Wang et al, 2012;Yang et al, 2014;Zhang et al, 2016), but increases the proliferation of prostate cancer cell lines (Voloshyna et al, 2008). A compound that enhances TREK-1 opening might help controlling pathological tissue remodeling associated with non-myocyte proliferation in the heart.…”
Section: Cell Type Selectivity Of Leca Bindingmentioning
confidence: 99%